Roles of Perivascular Adipose Tissue in the Pathogenesis of Atherosclerosis - Tanaka, Kimie; Sata, Masataka (Frontiers in Physiology, 2018)
Traditionally, it is believed that white adipose tissues serve as energy storage, heat insulation and mechanical cushion, whereas non-shivering thermogenesis occurs in brown adipose tissue. Recently, adipose tissue has been recognized as an endocrine organ that secretes many types of cytokines, called as adipocytokines, which modulate glucose metabolism, lipid profile, appetite, fibrinolysis, blood pressure, and inflammation. Most of the arteries are surrounded by perivascular adipose tissue (PVAT). PVAT has been thought to be simply a structurally supportive tissue for vasculature. However, recent studies showed that PVAT influences vasodilation and vasocontraction, suggesting that PVAT regulates vascular tone and diameter. Adipocytokines secreted from PVAT appear to have direct access to the adjacent arterial wall by diffusion or via vasa vasorum. In fact, PVAT around atherosclerotic lesions and mechanically-injured arteries displayed inflammatory cytokine profiles, suggesting that PVAT functions to promote vascular lesion formation. Many clinical studies revealed that increased accumulation of epicardial adipose tissue (EAT), which surrounds coronary arteries, is associated with coronary artery disease. In this review article, we will summarize recent findings about potential roles of PVAT in the pathogenesis of atherosclerosis, particularly focusing on a series of basic and clinical studies from our laboratory.